خلافت کے لیے قرشیت کی شرط اور علمائے ہند: The Condition of being Quraishi for the Caliphate and the Indian scholars - Khurshid Ahmed Nadeem (DIRAYAT, 2024)
It is known from some Hadiths of the Holy Prophet (PBUH) that the position of the caliphate and Imamate in the system of Islamic state is special for Quraysh. There have been four points of view about this among the scholars of the subcontinent. Firstly, it is necessary to be Qureshi for Khalifah. Secondly, the Caliphate is not proven for non-Qureshi. It is just news in Hadith. Thirdly, Qureshi must be a caliph. However, this is not a condition for "Sultan". Therefore, a nonQureshi can occupy the post of Sultan. Fourthly, the condition described is related to the practical demands and requirements of the politics of that specific period. Therefore, the Muslim scholars of the subcontinent did not deny the validity of the Hadiths regarding the Imamate of Quraish. It is a matter of understanding. Some scholars have considered these traditions in the light of their overall knowledge of Islam and derived meaning from them. It happens that the scholarly tradition of the subcontinent has progressed fully accepting the diversity of the Muslim Ummah.